Analisis Peluang Usaha Toko Pertanian di Beberapa Kecamatan Kabupaten Labuhan Batu - Ali Anjas Munthe; Yusmaidar Sepriani; Kamsia Dorliana Sitanggang (JURNAL MAHASISWA AGROTEKNOLOGI (JMATEK), 2021)
This study is entitled Analysis of Farm Shop Business Opportunities in Labuhan Batu District which aims to find the location of 9 sub-districts in Labuhan Batu Regency which are most likely to open a new farm shop business.This study uses a qualitative descriptive method by distributing questionnaires to farm shop owners that have existed in each district in Labuhan Batu Regency, namely Rantau Selatan, Rantau Utara, Bilah Hulu, Bilah Hulu Barat, Bilah Hilir, Pangkatan, Panai Hulu, Panai Tengah. and Panai Hilir.Samples were taken many as 37 respondents with 30 questions each. The results of this study stated that Panai Hilir District was the most likely location to open a new agricultural shop business because Panai Hilir sub-district became one of the largest rice granaries in Labuhan Batu District.Covering an area of 14,872.87 hectares of active agricultural land owned by the community, this sub-district is in dire need of agricultural materials such as fertilizer, pesticides, herbicides and other agricultural equipment. Based on the supporting data table, it can be sorted that the sub-district which has the most opportunity to open a new agricultural shop business is Panai Hilir(82%), Panai Hulu(68%), Panai Tengah(67%),Pangkatan(63%), Bilah Barat(61%), Bilah Hilir(60%), Bilah Hulu(60%), Rantau Selatan(55%), Rantau Utara(52%).                                Keywords: Business Opportunities, Labuhan Batu, Agricultural Shop